AB0631 Hypersensitivity to Rituximab: A Rapid and Simplified Desensitization Protocol for Patients with Anca-Associated Vasculitis and Other Autoimmune Disorders. (9th June 2015) - Berti, A.; Yacoub, M.-R.; Colombo, G.; Moiola, L.; Campochiaro, C.; Tomelleri, A.; Sabbadini, M.G.; Baldissera, E.; Dagna, L.
Abstract : Background: Rapid desensitization protocols for the treatment of drug hypersensitivities is aimed at preventing patients from moderate/severe hypersensitivity reactions (HRs) while providing essential medications. Recently, safety and success of rapid desensitization protocols have been broadly assessed for anti-cancer drugs, including some monoclonal antibodies. At the moment, however, no study addressed the issue of drug desensitization focusing on patients with autoimmune disorders Objectives: We intend to assess the efficacy and safety of a rapid desensitization protocol that we designed for patients with autoimmune diseases who experienced moderate/severe immediate HRs to rituximab (RTX). Methods: RTX infusion followed a standardized, 2-solution, 14-step protocol, which allowed for gradual increases in the infusion rate and drug concentration and allowed for the infusion of the target dose over 5 to 7 hours (depending on the total dose of the drug to be administered). The rate of the infusion was changed every 15 minutes, with each step delivering approximately twice the dose of the previous step (0.04 to 250 mg of RTX/h). The final step (Step 14) maintained a constant rate of infusion to deliver the remainder of the total dose. Patients received systemic steroids and anti-histamines at hour -12, -1, and +4 of RTX administration. The drug was administered in a sub-intensive care unit, with strict monitoring of the vital parameters until 6 hours after the last administration. Results: We treated so far 6 patients with autoimmune disorders who experienced previous moderate or severe HRs to RTX: 2 patients with granulomatosis with polyangiitis (GPA); 1 patients with microscopic polyangiitis (MPA) and 3 patients with neuromyelitis optica (NMO). All patients had detectable circulating serum levels of antibody directed against MPO or PR3 (for MPA and GPA) and AQP4 (for NMO). For all patients RTX was the only reasonable therapeutic alternative. All patients completed the desensitization protocol successfully and uneventfully. In one patient with NMO, the infusion rate was only temporarily reduced due to mild pruritus, which resolved promptly and allowed the completion of the treatment protocol. All the patients tolerated the following RTX treatment. Conclusions: These preliminary data support the adoption of a rapid desensitization strategy to treat patients with autoimmune disorder who experienced HRs to RTX. In particular, we are the first authors reporting the successful desensitization in patients with ANCA-associated vasculitis. Since only a mild reaction was noted during desensitization, our simplified protocol seems to be safer if compared to the already published protocols. Even though a larger cohort of patients will be needed to draw definitive conclusions, the proposed protocol preliminarily showed to be simple, safe and effective. References: Brown SG. J Allergy Clin Immunol. 2004 Aug;114(2):371-6. Castells MC, et al. J Allergy Clin Immunol. 2008 Sep;122(3):574-80. Brennan PJ, et al. J Allergy Clin Immunol. 2009 Dec;124(6):1259-66. Disclosure of Interest: None declared